To what extent are the mental health services available to asylum seekers and refugees being utilised and what barriers prevent access to these services? A systematic review. - Jones, Emily; Challiner, Alistair (Advanced Journal of Professional Practice, 2025)
Background: The number of refugees and asylum seekers in the United Kingdom is increasing. With NHS resources already under strain, the effective management of these patients is essential. Asylum seekers and refugees are at increased risk of mental health issues due to their experiences endured in their country of origin and whilst travelling to the UK, as well as stressors associated with settling in the UK. Despite this, ASR patients are less likely to receive mental health support. This systematic review aims to identify the barriers preventing effective mental health support for asylum seekers and refugees in the UK, in order to improve engagement with services and mental health outcomes in this population. Methods: The researcher followed the PRISMA guidelines to produce this systematic review. 15 papers were identified from searching the databases PubMed, Medline, Embase, Cochrane Library of systematic reviews, PsycINFO, British Nursing Index. Critical appraisal was then carried out on the papers, all of which were deemed high quality and valuable for the study. The researcher used thematic analysis to produce overarching themes presented by the included papers. Results: The overarching themes identified were: exclusion, healthcare professional factors, culturally sensitive care and practical barriers. 11 identified sub themes were amalgamated to produce these. These wider themes spoke to the significant barriers that prevent access to mental health care for this population. All 15 papers included point to multiple barriers for asylum seekers and refugees. Conclusions: There are multiple complex barriers for asylum seekers and refugees when accessing mental health support. These complex barriers are evidenced by the wide range of sub themes and the overarching themes identified. The researcher concludes that asylum seeker and refugee engagement with mental health services is low due to significant barriers that prevent access. Mental health services need to build relationships with the asylum seeker and refugee communities in the United Kingdom to enhance engagement in the service. Policy makers need to consider ways to reduce exclusion of this population and consider the impact of current policies on engagement in the service and attitudes towards this patient population.